2020
DOI: 10.1007/s00261-020-02825-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of bedside percutaneous biliary drainage in patients with severe cholangitis

Abstract: Purpose To evaluate the safety and feasibility of bedside percutaneous transhepatic biliary drainage (PTBD) as a salvage procedure in patients with severe cholangitis in the intensive care unit (ICU). Methods This retrospective study evaluated records of consecutive patients with severe cholangitis who were admitted in the ICU. Bedside PTBD was performed using ultrasound guidance. The level and cause of biliary obstruction were recorded. The technical success of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Most of the patients who failed to respond were on organ support in the ICU. Poor clinical outcomes in this group of patients have also been reported previously (12). EUS-biliary drainage (EUS-BD) is increasingly utilized as a salvage procedure in patients with failed ERCP (18).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Most of the patients who failed to respond were on organ support in the ICU. Poor clinical outcomes in this group of patients have also been reported previously (12). EUS-biliary drainage (EUS-BD) is increasingly utilized as a salvage procedure in patients with failed ERCP (18).…”
Section: Discussionmentioning
confidence: 54%
“…A recent study showed that PTBD could be performed safely at the bedside in patients with severe cholangitis in the ICU (12). There were a few limitations to our study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The latest small series ( n = 10) by Gupta et al also illustrated that bedside PTBD using USG alone is a safe and technically feasible procedure in critically ill patients. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Its clinical impact has been explored by various workers and is well established for the management of malignant biliary tract obstruction (MBTO) [4][5][6]. Advanced non-operable cases are most commonly referred for PTBD if there is pruritus, cholangitis, hilar level blocks, or failure of endoscopic retrograde cholangiography (ERCP) [7][8][9]. While PTBD is essentially considered a palliative procedure, it can decrease the bilirubin level significantly, leading to chemotherapy (CT) induction [4].…”
Section: Introductionmentioning
confidence: 99%